0784 Couples-based treatment for obstructive sleep apnea: perspectives from patients with mild cognitive impairment and their partners. (25th May 2022) - De Vettori, Giulia; Troxel, Wendy; Duff, Kevin; Dixon, Ava; Baron, Kelly
Abstract: Introduction: Patients with Mild Cognitive Impairment (MCI) have an increased risk of Obstructive Sleep Apnea (OSA) which may have implications for their cognitive function. Sleeping is often a shared behavior among couples, and for couples with MCI, partners often assume the role of caregiver. The goal of this study is to examine the role of bedpartners in adherence to treatment for OSA and to determine the feasibility for couples-based adherence interventions in individuals with MCI and their partners. Methods: This study is ongoing and will include semi-structured interviews with 10 couples. Interviews will be conducted remotely over Zoom, then transcribed and coded using Dedoose software to identify common themes among transcripts. Interviews discussed the impact of OSA and MCI on the couple with regard to CPAP treatment, interdependence of sleep, and feasibility of a couples-based CPAP intervention. Results: Currently, three out of 10 couples have been interviewed. The participants included three men and three women (mean age= 74 years). Themes from the interviews include significant involvement of partners in the treatment of OSA (e.g., reminders and ordering supplies). Couples felt that this program would have been helpful when they were beginning CPAP treatment. They provided suggestions for the format of a couples-based treatment in MCI including shorter sessions with more pictures and simplified content so that it could be better understood by the patient and partner. Conclusion: Data from these interviews demonstrate the critical role of the partner in adherence to CPAP treatment among patients with MCI. While interviews are currently ongoing, both patients and partners view couples-based sleep apnea treatment as feasible and adaptations will be made for this population. Couples-based treatments may be a promising intervention for increasing CPAP adherence in OSA patients with MCI, and further slowing cognitive decline. Support (If Any): NIA: #59317201